Konseling Keluarga untuk Meningkatkan Ketahanan Keluarga - Ulfiah Ulfiah (Psympathic : Jurnal Ilmiah Psikologi, 2021)
The background of this study is based on the significance of family counseling to increase family resilience. This counseling is needed to help families in dealing with complex family problems and involves many factors. The purpose of this study is to review the literatures on family counseling approach in increasing family resilience. This study uses a systematic literature review (SLR) approach from various articles that discuss family counseling, family resilience, and household problems. The author used 3 selection criteria for the literature study: periodization, keywords, and limitation. The results show that the family and family resilience must be seen as a system that has various influencing factors. The important role of family counseling is to help families in dealing with crisis situations, find the right solution, bring out the best potential, and develop the ability to work together.